A new clinical guideline from the Royal College of Paediatrics and Child Health with a national awareness campaign accelerates brain tumor diagnosis in UK children—"HeadSmart: Be Brain Tumour Aware". Issue 3 (1st November 2015) - ,; ,; Walker, David; Wilne, Sophie; Grundy, Richard; Kennedy, Colin; ,; Dickson, Angela; Lindsell, Sarah; Trusler, Julia; Evans, Alison; Dudley, Jan; et al.
Abstract: Background: A national survey in 2006 identified that UK referral practice for pediatric CNS tumors ranked poorly in international comparisons, which led to new National Health Service (NHS) Evidence accredited referral guidelines published in 2008 by the Royal College of Paediatrics and Child Health and a campaign to raise awareness of early features of CNS tumors and the need for timely imaging. Methods: The "HeadSmart: Be Brain Tumour Aware" campaign was launched in June 2011 across the UK as a quality improvement strategy directed at reducing the total diagnostic interval (TDI) from a pre-campaign (2006) median of 14 (mean, 35.4) weeks to a target of 5 weeks in order to equal the best reported internationally. Professional and public awareness was measured by questionnaire surveys. TDI was collected by clinical champions in 18 regional children's cancer centers and the public campaign was coordinated by a national charity, working with a network of community champions. Results: The guidelines and campaign raised awareness among pediatricians and were associated with reduction in TDI to a median of 6.7 (mean, 21.3) weeks by May 2013. This change in referral practice was most pronounced in the time from first medical contact to CNS imaging, for which the median was reduced from 3.3 to 1.4 weeks between January 2011 and May 2013 ( P = .009). Conclusion: This strategy to accelerate brain tumor diagnosis by the NHS using a public and professional awareness campaign is a "world first" in pediatric cancer and is being emulated internationally and acknowledged by a series of NHS and charity awards for excellence.